Measuring functional polycentricity for the analysis of structural places: The case of the seven principal metropolitan areas in Spain - Nancy Ruiz Estupi\~nán; Carlos Marmolejo Duarte; Moira Tornés Fernández (European Regional Science Association (ERSA), 2013)
The study of polycentrism has been applied over territory in order to identify and explain the components of the urban structure and the transformation of cities in large metropolitan systems, and its impacts on the social, demographic, economic and environmental issues. It is clear the need to go beyond the paradigm of monocentric city and conveniently to penetrate in the analysis of the current metropolis as large artifacts, composed by a series of settlements which are in fact related to each other. In practical terms, the study of polycentrism is responsible for identifying subcenters that integrate urban systems, as well as measuring the magnitude of the phenomenon in the urban reality. Meanwhile, in regard to the degree of polycentrism of an urban area, can be clearly identified two currents that have been widely studied, almost always independent of one another. The first is related to morphological analysis linked to the analysis of the density and shape of population distribution and employment in their cores and its hinterland. The second trend is related to the functional analysis tied to the study of flows that arise between different cores and its hinterland, linking functionally complementary areas. Integrating both tasks would lead to conclude that the coincidence of morphologic and functional polycentrism would be symptomatic of the existence of places that are not only dense, but also that structure territory and become structural places. A further development of the measurement of functional polycentrism is presented by Green (2007) proposing the 'functional polycentricity' concept, contrasting the term polycentrism related to the simple morphological polynucleation, from functional related to the network operation of the system. According to Green, functional polycentricity level is not defined by the proximity between nodes but by the relationship between them. Based on the methods of social network analysis, has proposed the indicator of 'network density' that attempts to measure how flows are balanced between the nodes: the more connected they are and such distribution is more uniform, the higher polycentricity functional level. This paper presents the analysis of measure of functional polycentricity for seven metropolitan areas in Spain, applying the functional polycentricity index for each one and further, finding its determinants, incorporating variables of magnitude, territorial balance and complexity to a linear regression model. It was found that from the functional perspective, the studied metropolitan areas of Spain have low levels of polycentricity. In order of magnitude was found to be less polycentric systems Zaragoza and Malaga; and in constrast Bilbao the largest, even over Barcelona. Was found also that, although the incipient index, the variables that can best explain it are flows and traveled distance, self-containment and specialization of the protosistems that conform metropolitan areas of Spain.
Keywords: R12; 330; Size and spatial distributions of regional economic activity